Building Structure With Seismic Design Categories Use SRPMK - Ade Maulana; Amirul Yusuf; Muchamad Rendy Santie Adhy; Arief Firmanto (Riviera Publishing, 2025)
In the planning of multi-storey buildings, safety and efficiency are crucial, particularly in designing structures capable of withstanding loads, including earthquake loads, which significantly impact building behavior. One method for withstanding earthquake loads is the design of moment-resisting frame systems, categorized into three types: ordinary moment-resisting frame system (SRPMB), medium moment-resisting frame system (SRPMM), and special moment-resisting frame system (SRPMK). The focus of this study is on structures that must endure extreme earthquake conditions, specifically the SRPMK and SRPMM systems, which are designed to withstand inelastic responses due to seismic activity, ensuring that the structure is ductile (flexible) and safe for use. The design process refers to SNI 2847-2019 and SNI 1726-2019 regulations and employs the ETABS 2020 program for modeling, analysis, and design. The analysis of the mall building revealed that the dimensions of the planned structural elements, such as beams and columns, meet the cross-sectional criteria for SRPMK and SRPMM systems, specifically the Strong Column Weak Beam design, are resistant to shear, and fulfill the detailed requirements for ductile structures. This study contributes to ensuring safer and more efficient building designs in seismic-prone areas.